The modulation of conceptual knowledge in memory retrieval in Alzheimer's Disease and Autism Spectrum Disorder: Examining the role of the hippocampus. - Souza, C.; Garrido, M. V.; Joana C. Carmo (8th IPRMS NeuroCom Summer School, 2018)
Memory is central to many cognitive processes, impacting in future decisions for a better social adaptation. For example, every day when we wake up, we plan our day based on long-term memories, as our previous experiences (episodic memory) and also as our general knowledge (semantic memory). Long-term memory theories suggest that the hippocampus sustains memories formation, but disagree upon the participation of this structure in all types of declarative memories. Also, the idea that hippocampus areas support the development of an abstract (semanticized) version of episodic memory traits in cortical areas remains in debate. In healthy individuals, the conceptual knowledge (i.e., schemas and item-typicality) enhances memory formation (episodic traits). However, in Autism-Spectrum-Disorder (ASD) and Alzheimer's Disease (AD) there is no benefit from the conceptual knowledge, specially item-typicality, when forming episodic memories. The possible explanation is because both clinical groups have hippocampus damage or alterations. This project examines the role of encoding schema (abstract mental representation) and item-typicality (goodness of an exemplar to represent it category) on episodic and semantic memories systems. We will contrast typical developmental (TD) adults with ASD-group as well as comparing AD-group with TD-elderly group in a recognition memory task with remember-know paradigm. The innovativeness of this proposal rests on indirectly comparing the neurocognitive profile of two clinical groups with robust behavioral and EEG neural measures. The project is likely to clarify the semantic-episodic system relationship, particularly the role of the hippocampus-cortical network, and to uncover neurocognitive signatures in these clinical populations for earlier diagnosis and rehabilitation purposes.